Reclamation of Post-Gold Mining Land Using Mycotrichocompost and Biochar: Effects on Corn (Zea Mays L.) Growth and Yield - Yummama Karmaita; Dara Latifa; Rita Wati; Ari Wahyuni; Risa Wentasari; Amda Resdiar; Nurholis Nurholis (Journal of Applied Agricultural Science and Technology, 2026)
Post-gold mining lands are severely degraded ecosystems requiring intensive restoration to recover their agricultural productivity and ecological functions. One promising approach to enhance soil biological, chemical, and physical properties is the application of biochar combined with mycotrichocompost. This study aims to evaluate the effects of biochar and mycotrichocompost on soil nutrient availability (N, P, K) and on the growth and yield of maize cultivated on post-gold mining soil.  The study used a factorial randomized block design: level 1 giving  Biochar (0 tons/ha, 4 tons/ha, 8 tons/ha, 12 tons/ha), and level 2 fertilizer application mycotrichocompost at different doses (0 tons/ha, 5 tons/ha, 10 tons/ha), resulting in 12 treatment combinations resulting in total 36 experimental units. Data were analyzed using analysis of variance (ANOVA), followed by Tukey's Honest Significant Difference (HSD) test at α = 0.05 using minitab 19. The addition of biochar and mycotrichocompost to former gold mining soil increased crop yields (9.93 tons/ha), plant growth (e.g., plant height: 152.3 cm and leaf length: 80.33 cm), physiological characteristics (e.g., chlorophyll a: 0.34 mg per gram of fresh leaf weight, chlorophyll b: 0.24 mg per gram of fresh leaf weight), and soil nutrient content (N: 0.14%, P: 271 ppm, and K: 1.87 ppm). In general, treatment A3B2 with a dose of 12 tons/ha of biochar plus 10 tons/ha of mycotrichocompost is the optimal combination.